THE PERCEIVED FUTURE EMPLOYABILITY OF EMPLOYED AND UNEMPLOYED STUDENTS FROM THE WEST UNIVERSITY OF TIMISOARA IN 2023 (PANGEEA, 2025)
The present study aims to identify the perceived future employability of the students enrolled at the West University of Timisoara in 2023, based on their personal characteristics. The sample consisted of 1442 valid answers of participants from 11 faculties. The methodological approach of the research is a quantitative one, the instrument used in the data collection process being an online questionnaire structured in six dimensions. The main results indicate a positive level of agreement with the perceived future skills, advantages and achievements stipulated in the questionnaire for all categories of students. The statistical tests emphasize a tendency for the teenagers who are studying, volunteering, but who are not working or not yet active on the labor market to be more optimistic towards their professional future in comparison with the ones who are already employed.
Keywords: perceived future employability; work readiness; university commitment; labor market